2010
DOI: 10.1080/02640410903428533
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical analysis of common lunge tasks in badminton

Abstract: The lunge is regularly used in badminton and is recognized for the high physical demands it places on the lower limbs. Despite its common occurrence, little information is available on the biomechanics of lunging in the singles game. A video-based pilot study confirmed the relatively high frequency of lunging, 15% of all movements, in competitive singles games.The biomechanics and performance characteristics of three badminton-specific lunge tasks (kick, step-in, and hop lunge) were investigated in the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 17 publications
5
128
1
3
Order By: Relevance
“…Performing a movement in jumping manner were shown to be more effective in force production and was in line with previous study of badminton lunge [10]. Larger peak vertical force during JFL could be related to the generation of extensor force by the knee joint to lift the leg off the ground for the jump phase prior to the secondary ground contact [10].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Performing a movement in jumping manner were shown to be more effective in force production and was in line with previous study of badminton lunge [10]. Larger peak vertical force during JFL could be related to the generation of extensor force by the knee joint to lift the leg off the ground for the jump phase prior to the secondary ground contact [10].…”
Section: Discussionsupporting
confidence: 72%
“…Larger peak vertical force during JFL could be related to the generation of extensor force by the knee joint to lift the leg off the ground for the jump phase prior to the secondary ground contact [10]. Several previous studies have found the advantageous of performing the lunge with jump movements [10,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Badminton players' ankles, knees and hips go through flexed and extended positions while maneuvering from mid-court to both court sides and forward and backwards to execute shots. Player's joints may be subject to high ground reaction forces, especially as the sport is performed on a hard surface [1].…”
Section: Introductionmentioning
confidence: 99%
“…Lunge is a movement that cannot be removed from movements of badminton players [8]. Due to the outbreak of arched plantar and sensitive feet in sports, especially in the sports which impose great force to the sole with fast speeds, it seems that injuries and their consequences can be prevented with preventive measures such as using shoes or the insole that are appropriate for sport and their structure is adequate to the distribution of forces and the player's feet shape.…”
Section: Introductionmentioning
confidence: 99%